1999
DOI: 10.1128/jvi.73.8.6670-6679.1999
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Integration of Human Immunodeficiency Virus Type 1 cDNA Ends by Purified Integrase In Vitro: Stimulation by the Viral Nucleocapsid Protein

Abstract: Integration of retroviral cDNA involves coupled joining of the two ends of the viral genome at precisely spaced positions in the host cell DNA. Correct coupled joining is essential for viral replication, as shown, for example, by the finding that viral mutants defective in coupled joining are defective in integration and replication. To date, reactions with purified human immunodeficiency virus type 1 (HIV-1) integrase protein in vitro have supported mainly uncoupled joining of single cDNA ends. We have analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 163 publications
(51 citation statements)
references
References 59 publications
1
50
0
Order By: Relevance
“…Several studies have explored the association between nucleosome packaging and integration bias. Early studies suggesting a loose association of retroviral integration sites with chromosomal sites sensitive to DNAseI digestion (reviewed in (16,19,20,34)), which led to the idea that packaging DNA in nucleosomes would inhibit integration. However, once assays were available that recapitulated integration in vitro, nucleosomal wrapping was found instead to favor integration (110)(111)(112)(113)(114).…”
Section: Retroviral Integration and Nucleosomal Associationmentioning
confidence: 99%
“…Several studies have explored the association between nucleosome packaging and integration bias. Early studies suggesting a loose association of retroviral integration sites with chromosomal sites sensitive to DNAseI digestion (reviewed in (16,19,20,34)), which led to the idea that packaging DNA in nucleosomes would inhibit integration. However, once assays were available that recapitulated integration in vitro, nucleosomal wrapping was found instead to favor integration (110)(111)(112)(113)(114).…”
Section: Retroviral Integration and Nucleosomal Associationmentioning
confidence: 99%
“…The mature NC protein, which is released in a late cleavage reaction (Swanstrom and Wills, 1997), plays a major role in assuring the specificity and efficiency of reverse transcription (reviewed in Bampi et al, 2004;Darlix et al, 1995;Levin et al, 2005;Rein et al, 1998; and is also important for other events in the virus life-cycle including maturation of the genomic RNA dimer (Feng et al, 1996;Muriaux et al, 1996) and integration of proviral DNA into the host genome (Carteau et al, 1999;Thomas et al, 2006). NC's function in virus replication is correlated with its ability to act as a nucleic acid chaperone.…”
Section: Introductionmentioning
confidence: 99%
“…Additional results by Gorelick et al also indicated that the integration reaction was impaired (Buckman et al, 2003;Thomas et al, 2006), supporting the view that functional interactions exist between NC and IN as it stands between NC and RT since mutating the ZF strongly diminish NC-RT interactions (Druillennec et al, 1999a;Lener et al, 1998). The existence of critical interactions between NC and IN is further supported by the fact that NC can strongly stimulate concerted LTR DNA integration by IN under physiological conditions in vitro (Buckman et al, 2003;Carteau et al, 1997Carteau et al, , 1999Poljak et al, 2003;Thomas et al, 2006).…”
Section: Impacts Of Zinc Finger Mutations On Viral Dna Synthesis and mentioning
confidence: 71%